Comparative Performance Analysis of Linear Precoding in Downlink Multi-user MIMO - Subuh Pramono; Eddy Triyono (IAES Indonesia Section, 2018)
This paper investigates the comparative performance of linear precoding schemes. The linear precoding schemes are including block diagonalization (BD), zero forcing (ZF), and maximum ratio transmission (MRT) in downlink multi-user MIMO. This work delivers the performance of linear precoding in term of achievable sum rate and bit error rate (BER) with a variation of the signal to noise ratio (SNR) and the number of transmitter-receiver antennas. We suppose that the transmitters have a complete channel state information. The results show that the MRT precoding yields better bit error rate than both the BD and ZF precoding schemes. However, the ZF precoding generates better achievable sum rate than the MRT precoding. In the other side, the MRT precoding also outperforms when the number of active users is bigger than Kcross while the number of active users is less than Kcross the ZF precoding is still dominant.